Microbial populations and activities of mangrove, restinga and Atlantic forest soils from Cardoso Island, Brazil - Pupin, B. [UNESP]; Nahas, E. [UNESP] (Wiley-Blackwell, 2014)
AimMangroves provide a distinctive ecological environment that differentiates them from other ecosystems. This study deal to evaluate the frequency of microbial groups and the metabolic activities of bacteria and fungi isolated from mangrove, restinga and Atlantic forest soils.Methods and ResultsSoil samples were collected during the summer and winter at depths of 0-2, 2-5 and 5-10cm. Except for fungi, the counts of the total, sporulating, Gram-negative, actinomycetes, nitrifying and denitrifying bacteria decreased significantly in the following order: Atlantic forest>mangrove>restinga. The counts of micro-organisms decreased by 11 and 21% from the surface to the 2-5 and 5-10cm layers, but denitrifying bacteria increased by 44 and 166%, respectively. A larger growth of micro-organisms was verified in the summer compared with the winter, except for actinomycetes and fungi. The average frequency of bacteria isolated from mangrove, restinga and Atlantic forest soils was 95, 77 and 78%, and 93, 90 and 95% for fungi, respectively. Bacteria were amylolytic (33%), producers of acid phosphatase (79%) and solubilizers (18%) of inorganic phosphate. The proportions of fungi were 19, 90 and 27%.ConclusionThe mangrove soil studied had higher chemical characteristics than the Atlantic forest, but the high salinity may have restricted the growth of microbial populations.Significance and Impact of the StudyEstimates of the microbial counts and activities were important to elucidate the differences of mangrove ecosystem from restinga and Atlantic forest.
Keywords: Bacteria; soil depth; Season; metabolic activity; Ecosystems; fungi